Expressions of vitamin D metabolic components VDBP, CYP2R1, CYP27B1, CYP24A1, and VDR in placentas from normal and preeclamptic pregnancies - Rong Ma; Yang Gu; Shuang Zhao; Jingxia Sun; Lynn J. Groome; Yuping Wang (2012)
Vitamin D insufficiency/deficiency during pregnancy has been linked to increased risk of preeclampsia. Placenta dysfunction plays an important role in the pathogenesis of this pregnancy disorder. In this study, we tested the hypothesis that disturbed vitamin D metabolism takes place in preeclamptic placentas. Protein expressions of vitamin D binding protein (VDBP), 25-hydroxylase (CYP2R1), 1α-hydroxylase (CYP27B1), 24-hydroxylase (CYP24A1), and vitamin D receptor (VDR) were examined in placentas from normotensive and preeclamptic pregnancies. By immunostaining we found that in normal placenta VDBP, CYP24A1, and VDR expressions are localized mainly in trophoblasts, whereas CYP2R1 and CYP27B1 expressions are localized mainly in villous core fetal vessel endothelium. Protein expressions of CYP2R1 and VDR are reduced, but CYP27B1 and CYP24A1 expressions are elevated, in preeclamptic compared with normotensive placentas. Because increased oxidative stress is an underlying pathophysiology in placental trophoblasts in preeclampsia, we further determined whether oxidative stress contributes to altered vitamin D metabolic system in placental trophoblasts. Trophoblasts isolated from normal-term placentas were treated with hypoxic-inducing agent CoCl 2 , and protein expressions of VDBP, CYP2R1, CYP27B1, CYP24A1, and VDR were determined. We found that hypoxia-induced downregulation of VDBP, CYP2R1, and VDR and upregulation of CYP27B1 and CYP24A1 expressions were consistent with that seen in preeclamptic placentas. CuZnSOD expression was also downregulated in trophoblasts treated with CoCl 2 . These results provide direct evidence of disrupted vitamin D metabolic homeostasis in the preeclamptic placenta and suggest that increased oxidative stress could be a causative factor of altered vitamin D metabolism in preeclamptic placentas.